Domain-specific associations between social cognition and aggression in schizophrenia spectrum disorders - Sarah A. Berretta; Lindsay D. Oliver; Courtland S. Hyatt; Ricardo E. Carrión; Katrin Hänsel; Aristotle Voineskos; Robert W. Buchanan; Anil K. Malhotra; Sunny X. Tang (Schizophrenia Research: Cognition)
Aggression in schizophrenia spectrum disorders (SSD) is rare but elevated relative to the general population. Existing studies have not identified reliable personal predictors of aggression in SSD. In line with social information processing models suggesting that difficulties interpreting social cues and others' intentions may lead to aggression, we evaluated whether social cognitive domains or global social cognition could be modifiable risk factors in SSD.We examined aggression and social cognition in 59 participants with SSD and 43 healthy volunteers (HV). Self-reported aggression was measured via the Reactive-Proactive Aggression Questionnaire (RPAQ). Social cognition was assessed using five tasks measuring emotion processing, theory of mind, and social perception. Group differences were analyzed using Mann-Whitney-Wilcoxon tests. Multiple regressions examined effects of social cognition on aggression, controlling for demographic and clinical covariates. Supplemental mediation analyses tested whether impairments in emotion processing, theory of mind, or overall social cognition explained the relationship between SSD diagnosis and increased aggression.Reported aggression was higher in the SSD group, and social cognitive abilities were impaired across domains (p < .001). Better emotion processing (β = −0.35, p = .03) and theory of mind (β = −0.32, p = .03) predicted lower aggression in SSD, even when accounting for demographic and neurocognitive variables. Exploratory models adjusting for overall psychiatric symptom severity showed that theory of mind remained significant, while emotion processing attenuated. However, social cognition did not mediate the relationship between diagnosis and aggression. Future studies should examine other social processing factors, such as attributional bias.